Cameras on Duty: Exploring the Impact of Body-Worn Cameras on Law Enforcement Practices and Accountability - Clarito, Mark Rovi A.; Lagumen, Henedina A. (Future Science / FSH-PH Publications, 2025)
This study examined the perceptions of the PNP personnel of Cabuyao Component City Police Station and barangay officials in different barangays in Cabuyao City, Laguna regarding the impact of body-worn cameras on law enforcement operations, practices, and accountability. This study analyzed significant differences in their responses concerning awareness of BWCs’ role in reducing crime, enhancing police accountability, and improving community trust. Additionally, the study explored challenges in the use of BWCs and assessed their effectiveness in preventing police misuse of force. This study employed descriptive quantitative research design, and the data gathered through questionnaires distributed to the police personnel and barangay officials from various barangays in Cabuyao City. Findings showed that PNP personnel and barangay officials recognized the benefits of BWCs in promoting transparency of their operations, reducing crime rates in high-crime prone areas, and strengthening community trust. Key challenges to effective implementation of BWCs include limited funding for purchasing, technical difficulties during police operations, and inadequate training in using BWCs. These results underscore the positive impact of BWCs in enhancing modern policing procedure. Addressing operational challenges and fostering alignment between law enforcement agencies and the public perspectives are therefore essential in achieving long-term positive impact.